Pengaruh Pengawasan, Pengalaman Kerja, dan Disiplin Kerja Terhadap Kinerja Pelayanan Pegawai ASN pada Kantor Kecamatan Percut Sei Tuan - Morena Deva Rosyah Putri Pakpahan; Ananda Fitriani Dewi (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
Employee service performance is the work results in terms of quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. Employee service performance is the spirit possessed by an employee in carrying out his work. To complete tasks and work, an employee should have a sense of willingness and a certain level of ability. In this study, the population is all ASN employees of the Percut Sei Tuan sub-district office, totaling 69 people. Based on the statement above, in determining the number of samples to be taken in this study, the author uses Saturated Sampling, because the number of ASN employees of the Percut Sei Tuan sub-district office is 69 people. Based on partial results of t count of supervision variable 6.766 > t table 1.99714 with a significance level of 0.000 < 0.05, supervision has a significant positive effect on employee performance, results of t count of work experience variable -2.496 > t table -1.99714 with a significance level of 0.015 < 0.05, work experience has a significant negative effect on employee performance, results of t count of work experience variable -2.496 > t table -1.99714 with a significance level of 0.015 < 0.05, work experience has a significant negative effect on employee performance, results of t count of work discipline variable 0.516 < t table 1.99714 with a significance level of 0.608 > 0.05, work discipline does not have a significant positive effect on employee performance, simultaneous testing of the estimated linear regression model is suitable for explaining Supervision (X1), Work Experience (X2), Work Discipline (X3) on Employee Service Performance (Y).